2006
DOI: 10.1172/jci26958
|View full text |Cite
|
Sign up to set email alerts
|

Senescence-associated phenotypes in Akita diabetic mice are enhanced by absence of bradykinin B2 receptors

Abstract: We have previously reported that genetically increased angiotensin-converting enzyme levels, or absence of the bradykinin B2 receptor, increase kidney damage in diabetic mice. We demonstrate here that this is part of a more general phenomenon -diabetes and, to a lesser degree, absence of the B2 receptor, independently but also largely additively when combined, enhance senescence-associated phenotypes in multiple tissues. Thus, at 12 months of age, indicators of senescence (alopecia, skin atrophy, kyphosis, ost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
1
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 61 publications
3
71
1
4
Order By: Relevance
“…9 Fibronectin secretion induced by macrophage-conditioned medium was reduced by perindoprilat or BK treatment. 10 In vivo, Akita diabetic mice with absent B2R had more severe albuminuria and glomerulosclerosis, 11 and senescence-associated phenotypes 12 attenuated the anti-proteinuric effect of ramipril. 13 More recently, Bodin et al 14 showed that KLK-knock out STZ-induced mice had more severe albuminuria than WT.…”
Section: Discussionmentioning
confidence: 99%
“…9 Fibronectin secretion induced by macrophage-conditioned medium was reduced by perindoprilat or BK treatment. 10 In vivo, Akita diabetic mice with absent B2R had more severe albuminuria and glomerulosclerosis, 11 and senescence-associated phenotypes 12 attenuated the anti-proteinuric effect of ramipril. 13 More recently, Bodin et al 14 showed that KLK-knock out STZ-induced mice had more severe albuminuria than WT.…”
Section: Discussionmentioning
confidence: 99%
“…The latter effect of kinins is also associated with their synergistic potentiation of IL-1-induced prostaglandin E 2 (PGE 2 ) and PGI 2 production (10,11). In addition to playing an important role in inflammationinduced bone remodeling, kinins are involved in senescence-associated bone loss, since mice double mutant for Ins2 Akita/ϩ and Bdkrb2 Ϫ/Ϫ genes exhibit a complex phenotype, including kyphosis and osteoporosis (12).…”
mentioning
confidence: 99%
“…Nous avons montré, chez le rat diabétique, que l'expression des récepteurs glomérulaires de certaines cytokines (IGF-1, insulin-like growth factor -1, TGF-β, transforming growth factor) est augmentée lors du blocage du RB2 [28]. Ces travaux sont par ailleurs en accord avec une observation récente indiquant que la surexpression du récepteur du TGF-β est augmentée chez les souris n'exprimant plus le RB2 [29].…”
Section: La Bk Module L'expression Et La Signalisation Des Récepteursunclassified
“…Une réduction de la formation de radical superoxyde et des concentrations sériques en triglycérides et cholestérol a été démon-trée après transfert du gène de la kallicréine [32][33][34]. Inversement, une aggravation du profil du stress oxydant a été décrite chez les souris n'exprimant pas le RB2 [29]. Enfin, chez le rat diabétique, notre groupe a décrit une augmentation de l'accumulation de protéines complexées à des dérivés 4-HNE (index de la peroxidation lipidique) lors du blocage du RB2 [28].…”
Section: La Bk Module L'expression Et La Signalisation Des Récepteursunclassified
See 1 more Smart Citation